Are idiopathic pulmonary fibrosis patients more anxious and depressive than patient’s with other interstitial lung disease? Anxiety and Depression in İnterstitial Lung Disease - Yalnız, Enver; Polat, Gulru; Ucsular, Fatma; Deniz, Sami; Karadeniz, Gulistan; Aydinli, Esra; Vayisoglu, Gorkem; Ayranci, Aysu (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease (ILD) with unknown etiology that occurs primarily in older adults with a median survival time of 2.5±3.5 years. Since there is no curative treatment for IPF, patients with IPF may have symptoms of depression and anxiety more than those of other interstitial  lung diseases. There is a few studies about comparison of anxiety depression with other interstitial lung disease and IPF. In this study, we investigated whether anxiety depression in IPF was more frequent than other ILDs and its effect on quality of life. Methods: The study was designed as a prospective study. Age, sex, smoking status, respiratory symptoms, comorbidities, pulmonary function tests, diffusion capacity of the lungs for carbon monoxide (TLCO), SF-36, and depression/anxiety levels, radiological findings, erythrocyte sedimentation rate (ESR), CRP level, blood gas analysis, complete blood count parameters were recorded. Results: The mean age of 50 IPF and 42 non-IPF interstitial lung disease patients were 67.4±7.1 and 64.9±7.2, respectively. Compared with the non-IPF group, SF-36 total, SF-36 physical function and SF-36 physical role severity were significantly lower in the IPF group, while the GAP score was significantly higher. There was no significant difference between the two groups in HAM-Anxiety and HAM-depression for total scores. But mild anxiety was present in most of non-IPF group. No severe anxiety was observed in this group. Forty-nine of 50 patients with IPF patients had moderate-severe anxiety and the difference was statistically significant compared to non-IPF patients. Conclusions: This is one of the first studies of anxiety and depression symptoms are also important in non IPF ILD like IPF. Patients with non-IPF ILD have similar anxiety depression with IPF patients in this study. This study led to the conclusion that anxiety depression should also be evaluated in non-IPF ILD patients.